Ekstrak Cacalincingan (Oxalis barrelieri L) Sebagai Antibakteri Terhadap Staphylococcus aureus dan Escherichia coli Penyebab Mastitis Sapi Perah - Pazra, Debby Fadhilah; Multida, Ikhwan; Nurlita, Siti; Sari, Mutia (Jurnal Veteriner, 2023)
Cacalincingan (Oxalis barrelieri L) has a role as an antibacterial because it has contain flavonoids, tannins, saponins, phenols and essential oils. The use of Cacalincingan plant extracts as antibacterial against bacteria that cause mastitis in dairy cows has not been widely studied, so the research needs to be done. The purpose of this study was to determine the effectiveness of Cacalincingan plant extract as an antibacterial against Staphylococcus aureus and Escherichia coli bacteria which are the cause of mastitis in dairy cows. The study used a completely randomized design with seven treatments and three replications to test inhibitory ability using wells diffusion method. The treatments consisted of various concentrations of Cacalincing plant extracts ranging from 5% (P1), 10% (P2), 15% (P3), 20% (P4), 25% (P5), 30% (P6) and 10% Iodine (P0) as controls +. The results showed that there was highly significant effect (P<0.05) in each concentration of Cacalincingan extract against growth inhibition of S. aureus and E. coli bacteria. The best inhibitory ability was found at a concentration of 30% with strong inhibition category on S. aureus and moderate category on E. coli, even the inhibition formed was more than 10% Iodine. This indicates that the Cacalincingan plant extract has effectiveness as an antibacterial against S. aureus and E. coli bacteria that cause mastitis in dairy cows. Based on these, Cacalincingan plant extract could be an alternative natural antiseptic to dip nipple in dairy cows so hopefully the incidence of mastitis in dairy cow can be decreased.